PROJETOS ARQUITETÔNICOS INOVADORES: A SINERGIA ENTRE DESIGN E FUNCIONALIDADE NA ENGENHARIA DE PROJETOS RESIDENCIAIS E CORPORATIVOS (REMUNOM, 2025)
This work investigates the synergy between design and functionality in the engineering of residential and corporate projects, with the aim of understanding how the integration of these two elements can improve the efficiency, sustainability and adaptability of architectural and structural projects. The research addresses fundamental concepts of architecture and civil engineering, as well as the evolution of architectural projects over time, presenting the importance of the interaction between aesthetics and functionality in the creation of spaces. To this end, two case studies are analyzed: Casa Grelha, located in São Paulo, Brazil, and BedZED, in London, UK, both of which are examples of how design and engineering practices can be applied synergistically, prioritizing efficiency and sustainability.